THE USE OF DIALOGUE JOURNAL TO IMPROVE DESCRIPTIVE WRITING ACHIEVEMENT OF THE EIGHTH GRADE STUDENTS OF MTS NEGERI 1 PALEMBANG - Ghina Salsabila; Margaretha Dinar Sitinjak; Rita Hayati (Sriwijaya University Learning and Education International Conference, 2018)
The objectives of this study were to find out whether or not: 1) there was any significant difference in descriptive writing achievement between the eighth grade students of MTs N 1 Palembang who were taught by using dialogue journal and those who were not and 2) whether or not there was any significant difference in descriptive writing achievement before and after the eighth grade students of MTs N 1 Palembang were taught by using dialogue journal. There were 60 students of eighth grade taken as the sample. They were divided into control and experimental groups which both of the groups were 30 students. The technique of selecting the sample was purposive sampling method. In collecting the data, both groups were given pretest and posttest. The data were analyzed by using Paired Sample t- Test and Independent sample t- Test. The results obtained from Paired Sample t- Test showed that there was a significant difference in students’ writing achievement before and after the students were taught by using dialogue journal since the ????-value was lower than 0.05 (0.000 < 0.05). The results obtained from Independent Sample t- Test of the posttest in both experimental and control groups showed that there was a significant difference in descriptive writing achievement between the students who were taught by using dialogue journal and those who were not as the ????-value lower than 0.05 (0.000 < 0.05). So, dialogue journal was effective to be applied in teaching descriptive writing for the eighth grade students of MTs N 1 Palembang.